Efeito do Lactobacillus reuteri no tratamento da doença periodontal experimentalmente induzida em ratos submetidos à quimioterapia com 5-fluorouracil: análise histométrica - Santos Neto, Otavio Marino dos [UNESP] (2016)
The objective of this study was to evaluate by histometric analysis, the effects of the systemic use of the probiotic (PRO) Lactobacillus reuteri in the treatment of experimental periodontitis (EP) in rats subjected to 5-fluorouracil chemotherapy. 54 rats were subjected to induction of experimental periodontitis (EP). The 5-FU was injected into the animals on the day of ligation installation (60 mg / kg) and 48 hours later (40 mg / kg). After 7 days of induction, the ligature was removed, and the animals were divided into 3 groups of 18 animals each: Group 5-FU/EP: animal treated with 5-FU and no local treatment; Group 5-FU/EP/SRP: animal treated with 5- FU and SRP; Group 5-FU/EP/PRO: animals treated with 5-FU, SRP and 4 gavagens with an interval of 48 hours of Lactobacillus reuteri. The animals were euthanized at intervals of 7, 15 and 30 days after treatment. Samples of the hemi-jaw underwent histological analysis and stained with Hematoxylin and Eosin. The area of bone loss (BL) in the furcation region of the molar was histometrically analyzed. The data were submitted to statistical analysis (α = 5%). The analysis of histometric data revealed that BL was lower in animals of 5-FU/EP/PRO group compared to 5-FU/EP and 5- FU/EP/SRP groups at 7, 15 and 30 days. It was concluded that systemic therapy using Lactobacillus reuteri as an adjunct to SRP is effective in the treatment of EP in rats subjected to 5-FU chemotherapy